Review on the generation, characteristics and control methods of indoor ozone pollution - Wang, Jun; Wang, Qi; Wang, Tingting (Frontiers in Built Environment, 2026)
Under the dual effects of outdoor ozone (O3) pollution intrusion and indoor pollution source generation, the formation mechanism, characterization, prevention and control methods of indoor O3 pollution have been one important scientific issue in the field of indoor air quality (IAQ) research. To have a systematic understanding of this issue, this study summarizes the trends and hotspots of indoor ozone pollution research, systematically reviews the sources, hazards, and characteristics of indoor ozone pollution and analyzes the different prevention and control methods of indoor ozone pollution, including active and passive ozone removal technologies. On this basis, the engineering applications of indoor ozone pollution prevention and control methods in residential, educational, and commercial scenarios are further discussed. Furthermore, the development trends and technical challenges of indoor ozone pollution prevention and control are pointed out. The development of efficient and low-cost ozone removal materials, the optimization of intelligent monitoring systems, and integrated pollution control strategies adapted to climate change should be focused on in the future, in order to provide healthier and safer indoor air environment. The insights could inform designers, engineers, and policymakers seeking to integrate ozone-responsive strategies into building ventilation, material selection, IAQ management, and air-cleaning systems.